Die Bleifunde der rȯmisch-republikanischen Anlage von Sanisera, Menorca : Archäologische und archäometrische Analyse - Müller, Regine (Archaeopress Roman archaeology, 2018)
This text presents archaeological and archaeometrical analysis of the lead finds from the Roman Republican military fort of Sanisera, northern Minorca. It places Sanisera within the historical context of the development of the late Roman Republic and early Imperial times